Analisis Perencanaan Manajemen Komunikasi Sumber Daya Manusia Di Rumah Sakit Umum Daerah Indrasari Rengat (Literatur Review) - johan, dwiyumelia (Komunika : Jurnal Ilmiah Komunikasi, 2023)
This study discusses the analysis of human resource (HR) communication management planning at the Indrasari Rengat Regional General Hospital through a literature review. The main objective of this research is to analyze how HR communication management planning is implemented in the hospital context. A comprehensive literature review was used to identify key concepts related to HR communication planning, as well as the factors that influence the success of their implementation. The results of this study reveal that HR communication management planning has a crucial role in achieving optimal efficiency, coordination and productivity in hospitals. Factors such as internal communication, use of information technology, effective leadership, and active HR participation are important elements in designing a successful communication planning strategy. In addition, challenges in dealing with dynamic changes in the hospital environment must also be considered in HR communication planning. This study provides an in-depth view of the practice of HR communication management planning in hospitals, by describing a conceptual framework that can assist hospital management in increasing the effectiveness of internal and external communications and optimizing the utilization of human resources. Further research can be conducted to observe the direct implementation of the HR communication planning strategy in this hospital and its impact on overall organizational performance.